Pengaruh Kompres Hangat Terhadap Nyeri Persalinan - R Siska Ramadhani; Nurun Nikmah (IJMT : Indonesian Journal of Midwifery Today, 2022)
Pain in labor is a characteristic interaction caused by the shortening of the uterine muscles and these contractions causing pain. Childbirth sometimes makes mothers feel traumatized because of the pain caused during the delivery process. However, it was found that about 80% of mothers felt unbearable pain and 20% felt slight pain. The method uses pre-experimental with one group pretest posttest design. The independent variable of this study was warm compresses and the dependent variable was pain reduction. The population is 15 mothers giving birth with a large sample of 14 respondents. . The sample in this study were mothers who experienced labor pain in the first stage of the active phase. This study using purposive sampling technique. This research took place at PMB Eko Wahyuningsih, Amd.Keb in May 2021. Statistical test using Paired T-test with 0.05. The results before being given a warm compress, almost half of the respondents felt the level of pain was very disturbing with a score of 8 as many as 6 people (42.86%), after being given a warm compress almost half of the respondents felt the level of pain was a bit disturbing with a score of 4 as many as 6 people ( 42.86%. From the Sample Paired T-test, it was obtained (p value = 0.000 <ɑ = 0.05) then H1 was accepted, which means that there is an effect. Pain in labor is a characteristic interaction caused by the shortening of the uterine muscles and these contractions causing pain. Childbirth sometimes makes mothers feel traumatized because of the pain caused during the delivery process. However, it was found that about 80% of mothers felt unbearable pain and 20% felt slight pain. The method uses pre-experimental with one group pretest posttest design. The independent variable of this study was warm compresses and the dependent variable was pain reduction. The population is 15 mothers giving birth with a large sample of 14 respondents. . The sample in this study were mothers who experienced labor pain in the first stage of the active phase. This study using purposive sampling technique. This research took place at PMB Eko Wahyuningsih, Amd.Keb in May 2021. Statistical test using Paired T-test with 0.05. The results before being given a warm compress, almost half of the respondents felt the level of pain was very disturbing with a score of 8 as many as 6 people (42.86%), after being given a warm compress almost half of the respondents felt the level of pain was a bit disturbing with a score of 4 as many as 6 people ( 42.86%. From the Sample Paired T-test, it was obtained (p value = 0.000 <ɑ = 0.05) then H1 was accepted, which means that there is an effect.